Fog as a source of nitrogen for redwood trees: evidence from fluxes and stable isotopes. (November 2015) - Templer, Pamela H.; Weathers, Kathleen C.; Ewing, Holly A.; Dawson, Todd E.; Mambelli, Stefania; Lindsey, Amanda M.; Webb, Jeramy; Boukili, Vanessa K.; Firestone, Mary K.; Austin, Amy
Summary A defining feature of the redwood forest in coastal California is the presence of fog in the summer months, a time when there is typically little rainfall. Our goal was to determine the role of summer fog in canopy transformation of nitrogen, nitrogen uptake by trees and photosynthesis within a coastal redwood forest ecosystem. We measured horizontal and vertical inputs of nitrogen, the isotopic composition of nitrogen in a variety of atmospheric sources (summer fog, winter rain and throughfall throughout the year), nitrogen pools (soil solution) and plant tissue (roots and foliage), as well as rates of photosynthesis and nitrogen uptake by trees. Throughfall nitrogen fluxes were greater at the forest edge compared to the interior both within the canopy (sampled 10 m above‐ground) and onto the forest floor (sampled 1 m above‐ground; P < 0.05). Similarly, soil solution <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkrnk1tz8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives> and total inorganic nitrogen were greater at the forest edge compared to the interior (P = 0.0014 and 0.009, respectively). Whereas natural abundance δ15NO3 values were not significantly different between winter rain (measured as bulk precipitation) and summer fog water (average δ15N = −1.2 ± 0.680/00), δ15NH4 values were significantly greater in fog water (11.4 ± 2.70/00) compared to rain (1.2 ± 0.90/00). We found no difference in δ15N in roots from forest edge trees compared to interior trees. In contrast, nitrogen concentrations and δ15N in foliage from forest edge trees were significantly greater compared to interior trees (P < 0.0001), suggesting that the leaves of forest edge trees may be obtaining a greater proportion of their nitrogen from fog compared to those of the interior trees. Natural abundance 13C of leaf sugars and rates of photosynthesis were significantly higher at the forest edge compared to the interior during the fog season (P < 0.05), but not different between locations in the rain season (P > 0.05). Nitrification in the forest floor, rather than the canopy, is the primary source of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkrnk1v1s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−</alternatives> in these soils throughout the year. Synthesis. Summer fog provides nitrogen directly and indirectly to redwood trees, especially those at the forest edge, and affects the physiologic function of redwood trees.